Evaluación de dos métodos de extracción de pectina de la cáscara de cacao (theobroma cacao) - Rengifo Álava, Yandry Javier (2019)
From cocoa shells; of the national variety EET103, applying two extraction methods: acid and enzymatic, the objective was to obtain pectin, whose yields were compared by t-Student to identify the most efficient method; additionally, physical-chemical analyses were carried out such as: solubility, gelling capacity, swelling capacity, water retention capacity, oil adsorption capacity and degree of esterification. The functional groups were characterized by infrared spectrophotometry with representative peaks. The mean comparison showed a significant difference (p≤0,05) between the methods, determining that the acid extraction reported higher yields; the physical-chemical parameters evidenced the following results: solubility 23,69% in enzymatic and 23,40% in acid. The spectrophotometer analysis determined areas (cm-1) in the acid and enzymatic extraction pectins of 1720,47 and 1727,98 respectively in the esters group, 1632,10 and 1600,99 in the acids group, compared with 1741,07 and 1637,95 in the commercial pectin, the pectin GE was 51,31% in acid and 51,90% in enzymatic; values were expressed in gH2O/gpectin, GC of 2.28 acid and 1.35 enzymatic, CRA is 1.86 for acid, 3.21 for enzymatic, for CAA is 0.31 for acid, 0.43 enzymatic and CH in acid 1.25 and 2.5 in enzymatic. To conclude, the acid extraction method performed better, but the enzyme provided better solubilities and functional characteristics; and the characterization peaks of the functional groups share similarities with the peaks of commercial pectin.